1996
DOI: 10.1108/eum0000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Developing key account management competences

Abstract: Argues that key account management (KAM) in industrial and business‐to‐business markets has its roots in sales management where it has long been recognized that customers of strategic importance require special treatment. Explains that, more recently, growing interest among academics and practitioners in relationship marketing has forced KAM centre stage as one of the few seemingly tried and tested approaches to customer retention and development, but that this trend has exposed three interrelated problems for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 11 publications
0
36
0
1
Order By: Relevance
“…By using the ecosystem approach, the customer's business will benefit not only in fulfilling their requirement but also their stakeholders requirement (mainly their suppliers, partners and customers). Millman and Wilson [8] describe this fulfillment of customers' needs in key account management as product need, process need, and facilitation need (the way in which business is done, rooted in joint problem solving and mutual adaptation).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the ecosystem approach, the customer's business will benefit not only in fulfilling their requirement but also their stakeholders requirement (mainly their suppliers, partners and customers). Millman and Wilson [8] describe this fulfillment of customers' needs in key account management as product need, process need, and facilitation need (the way in which business is done, rooted in joint problem solving and mutual adaptation).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…shortening learning curve, avoiding formal tenders, and improving forecasting) [2]. There are three orders of customer need that have to be fulfilled in KAM: Product need, Process need, and Facilitation need [8].…”
Section: A Key Account Management (Kam)mentioning
confidence: 99%
“…Madill et al (2007) posited that ''flexibility'' vis-à-vis an organization's willingness to modify its core operations and outlooks in order to better suit a key client was a critical element of successful SAM. Adaptations can occur in relation to the range and content of the services provided (Ojasalo 2001), internal organization structure (Millman and Wilson 1996), communication methods, or management style (McDonald et al 1997). Wallis and Dollery (2006) observed how the government (especially local government) was obliged ''to provide welfare services on a universal and uniform basis,'' regardless of the service preferences of contracted suppliers (p. 493).…”
Section: Sam Methodsmentioning
confidence: 99%
“…A survey completed by Feiock and Jang (2007) of 1,512 VOs with local government contracts in the USA revealed that more than half had attempted to change their management style to be more outcome-orientated in consequence of undertaking local government contract work. Critics have suggested that servicing government contracts distracts VOs from their true missions, prevents VOs from satisfying the needs of other stakeholders, and causes resentment among nongovernmental funders about the fact that a government body is receiving special attention (Millman and Wilson 1996). Managers of VOs frequently worry, it has been alleged, that ''simply taking public money'' makes them ''susceptible to political control, censure or government influence that diminishes their autonomy'' (Chau andHuysentruyt 2006, p. 1912).…”
Section: Sam Methodsmentioning
confidence: 99%
See 1 more Smart Citation